Symbolical Expression of Human Struggle in Hemingway’s Novel – The Old Man and the Sea: Decoding Symbolism and Interpretations in Hemingway's Masterpiece (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Masterful writers use literary devices and strategies exceptionally to represent their mastery and mastery of writing. In American writing, Ernest Hemingway's novel The Old Man and the Sea is a precious symbolic novel that reflects the ability of the author to use images and symbols to give an artistic quality to the content. The aim of this research paper is to explore the images used as part of the novel and to decode these symbols, as well as to distinguish between the different interpretations that they represent.